2020
DOI: 10.1021/acs.oprd.0c00224
|View full text |Cite
|
Sign up to set email alerts
|

Potential for the Formation of N-Nitrosamines during the Manufacture of Active Pharmaceutical Ingredients: An Assessment of the Risk Posed by Trace Nitrite in Water

Abstract: Regulatory requests that marketing authorization holders for chemically synthesized active substances risk assess their medicines for the potential presence of N-nitrosamines have led to a renewed interest in amine nitrosation. We have used published mechanistic and kinetic studies of amine nitrosation to assess the risk that traces of nitrite in the water used during active pharmaceutical ingredient (API) manufacturing could give rise to significant levels of N-nitrosamines. We conclude that the levels of nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 63 publications
1
107
0
Order By: Relevance
“…Having established a protocol using various chloride sources, we turned our attention to explore the scope of the aminoheterocycle (Table 1). First, we engaged a panel of 4-and 2-aminopyridines (7,(12)(13)(14)(15)(16)(17)(18)(19)(20). Tuning the temperature turned out to be crucial to achieve satisfactory yields and accommodate functionalities such as halides (12,14), aromatic rings (16,17), an ester (15), a morpholine (18), a nitro (19) or a cyano (20).…”
Section: Deaminative Chlorination Of Aminoheterocyclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Having established a protocol using various chloride sources, we turned our attention to explore the scope of the aminoheterocycle (Table 1). First, we engaged a panel of 4-and 2-aminopyridines (7,(12)(13)(14)(15)(16)(17)(18)(19)(20). Tuning the temperature turned out to be crucial to achieve satisfactory yields and accommodate functionalities such as halides (12,14), aromatic rings (16,17), an ester (15), a morpholine (18), a nitro (19) or a cyano (20).…”
Section: Deaminative Chlorination Of Aminoheterocyclesmentioning
confidence: 99%
“…First, we engaged a panel of 4-and 2-aminopyridines (7,(12)(13)(14)(15)(16)(17)(18)(19)(20). Tuning the temperature turned out to be crucial to achieve satisfactory yields and accommodate functionalities such as halides (12,14), aromatic rings (16,17), an ester (15), a morpholine (18), a nitro (19) or a cyano (20). Diazines, including pyrimidine ( Sandmeyer's limitations include explosive diazonium intermediates, limited functional group tolerance preventing its use for late-stage applications and being challenging for five-membered N-heterocycles.…”
Section: Deaminative Chlorination Of Aminoheterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The nitrosylation of DMA to generate NDMA was used as a model reaction that could rise during API processing. Simulations based on the published kinetics of secondary amine nitrosylation have shown that higher nitrite levels may result in significant levels of N -nitrosamines at low pH or elevated temperature [ 10 ]. Therefore, limiting the two precursor compounds in drug substances or products can prevent the potential formation of NDMA and other nitrosamines.…”
Section: Introductionmentioning
confidence: 99%
“…However, if excess of sodium nitrite were taken by eating foods containing nitroso compounds, N-nitrosamine, a carcinogen, might be produced by combining sodium nitrite and amino acids or secondary amines in human's digestive system [8][9]. Furthermore, processed meats are classified as carcinogens by the World Health Organization (WHO) [10].…”
Section: Introductionmentioning
confidence: 99%